Interference detection and diversity suppression algorithm of OFDM system under partial-band jamming - Guo LI; Ni WEN; Fengkui GONG; Jian ZHANG; Sihan ZHANG (Tongxin xuebao)
For the currently widely-used OFDM system, which greatly improved the communication performance under the condition of partial-band jamming, an interference detection algorithm based on FCVE and an interference suppression algorithm based on frequency diversity were proposed.The threshold factor formula of FCVE algorithm was derived theoretically, and the interference detection threshold was calculated by using the threshold factor and the variance of the received signal, so as to achieve the interference detection with high accuracy.The simulation results show that the proposed FCVE algorithm significantly improves the interference detection probability of the classical FCME algorithm under the condition of high signal to interference ratio (SIR).Further, the interference can be greatly suppressed based on the idea of frequency diversity with the result of interference detection.The simulation results show that the bit error rate of the system can be reduced by two orders of magnitude under the same SIR.